Application of Culturally Responsive Transformative Teaching (CRTT) Assisted by Podcasts and E-Assessments to Improve Student Creativity and Science Literacy - Puput Dyah Nur Safitri; Sri Yamtinah; Antuni Wiyarsi; Hayuni Retno Widarti; Ari Syahidul Shidiq (Vidya Karya, 2026)
This study investigated the impact of the influence of the Culturally Responsive Transformative Teaching (CRTT) Model, assisted by podcasts and e-assessments, on students' creativity and science literacy abilities in reaction rate materials. Quasi-experimental design with a cluster random sampling technique to select experimental classes and a control group from a public high school in the city of Karanganyar. Descriptive and inferential analyses were conducted by the Mann-Whitney test for the testing of the creativity hypothesis with significant results (<0.05), the independent samples t-test for testing the science literacy hypothesis with significant results (<0.05), and the Kruskal-Wallis test for the simultaneous hypothesis of two variables with significant results (<0.05). In conclusion, the podcast-assisted CRTT model and e-assessment on reaction rate materials can affect students' creativity and science literacy skills. In addition, this model includes culture-based learning equipped with podcasts as a flexible media facility, and e-assessments provide ease of assessment. These findings support the use of a podcast-assisted CRTT model and e-assessment as effective tools for enhancing chemistry learning, boosting students’ motivation, and improving their skills in line with the demands of 21st-century education.